Endoscopic "Quick" Septoplasty in Preservation Rhinoplasty. Issue 2 (February 2021) - D'Ascanio, Luca; Ori, Michele; Finocchi, Valerio; Vione, Nicola; Capalbo, Maria; Ricci, Giampietro
Abstract : Background: Preservation rhinoplasty (PR) is revolutionizing rhinoplasty surgery, based on new anatomical studies, advanced tip suture techniques, and refinement of surgical techniques. Septal surgery is a fundamental preparatory stage during PR, especially for the dorsal preservation let/push-down procedure. To increase the predictability of the septoplasty aesthetic effects on the nasal dorsum and further extend the principles of PR to septal surgery, we applied the endoscopic technology to the "quick" septoplasty technique we had already developed in the past decades. Methods: One hundred sixty-six patients (41 males, 125 females; mean age, 39.7 years; age range, 18–61 years) were submitted to endoscopic "quick" septoplasty for septal deviation during PR procedure. Preoperative evaluation of the nasal dorsum included external examinations of the size, shape, and orientation of the dorsum. Anterior active rhinomanometry was performed in all patients to determine nasal flow resistance preoperatively and 6 months after surgery. Preoperative and postoperative patients' scores on the Nasal Obstruction Septoplasty Effectiveness questionnaire were compared to assess the improvement of nasal symptoms after surgery. The duration of the septoplasty procedure was measured for all the patients. Standard nasal photographic assessment was performed before and 6 months after surgery. Results: Postoperatively, 98.8% of our patients displayed an improvement of their nasal breathing function. No complication in terms of septal perforation, nasal infection, or bleeding was noticed. No case of turbinoseptal synechiae or cerebrospinal fluid leak was recorded. The dorsum preservation rhinoplasty procedure was successfully completed in all patients. The mean septoplasty operative time, excluding local anesthesia injection and other surgical procedures associated with septal surgery such as turbinoplasty and rhinoplasty, was 11.41 ± 6.23 minutes (range, 9–31 minutes). Conclusions: Our results show that a short surgical time is needed to perform the proposed endoscopic septoplasty procedure. Such a short operative time allows the physician to both correct septal deviations quickly and correct/reduce the cartilaginous hump, thus representing a fundamental element of PR. In addition, the minimal tissue dissection reduces intraoperative nasal edema, favoring intraoperative aesthetic evaluation. Abstract : Supplemental digital content is available in the text.